Legal Protection of Indigenous Community in Protected Forest Areas Based Forest City - Mohammad Jamin; Abdul Kadir Jaelani; Duc Quang Ly; Kerry Gershaneck (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2022)
Indonesia has established regulations regarding the location of the National Capital. However, the important question is whether the Law is effective and whether the transfer of the National Capital has provided legal protection for indigenous peoples in the area designated as the National Capital. This study aims to analyze the protection of customary law communities in urban forest-based protected forest areas. This research is normative legal research, which uses secondary data with primary, secondary, and tertiary legal materials. The study results show that the state must finalize the Law on the State Capital, which also regulates the legal protection of Indigenous Peoples as a lex specialis provision. The Law on the State Capital must formulate norms that automatically guarantee the determination of the legal status of indigenous and tribal peoples.